2014
DOI: 10.1021/om500973b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanometer-Sized Cylinder-Like Structures from a 1,3,5-Triphenylbenzene-Bridged Tris-NHC Ligand and AgI, AuI, and CuI

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 68 publications
2
26
0
4
Order By: Relevance
“…We have previously observed that assemblies of type [Au 3 ( L ) 2 ](BF 4 ) 3 ( L =tris‐NHC ligand with a 1,3,5‐triphenylbenzene‐backbone), where tris‐NHC ligand L is closely related to A1 and D1 , feature two nearly coplanar orientated central benzene rings within two concave distorted tris‐NHC ligands. The concave distortion allows the central benzene rings to approach each other (centroid⋅⋅⋅centroid distance 3.644 Å, cf C NHC ⋅⋅⋅C NHC separation at the C NHC −Au−C NHC groups ≈4.0 Å) with formation of π⋅⋅⋅π stacking interactions . Similar, but much stronger π⋅⋅⋅π stacking interactions can be assumed between the triazine acceptor in A1 and the benzene donor in D1 of [Ag 3 ( A1 )( D1 )](BF 4 ) 3 .…”
Section: Figurementioning
confidence: 93%
See 2 more Smart Citations
“…We have previously observed that assemblies of type [Au 3 ( L ) 2 ](BF 4 ) 3 ( L =tris‐NHC ligand with a 1,3,5‐triphenylbenzene‐backbone), where tris‐NHC ligand L is closely related to A1 and D1 , feature two nearly coplanar orientated central benzene rings within two concave distorted tris‐NHC ligands. The concave distortion allows the central benzene rings to approach each other (centroid⋅⋅⋅centroid distance 3.644 Å, cf C NHC ⋅⋅⋅C NHC separation at the C NHC −Au−C NHC groups ≈4.0 Å) with formation of π⋅⋅⋅π stacking interactions . Similar, but much stronger π⋅⋅⋅π stacking interactions can be assumed between the triazine acceptor in A1 and the benzene donor in D1 of [Ag 3 ( A1 )( D1 )](BF 4 ) 3 .…”
Section: Figurementioning
confidence: 93%
“…The olefin substituents were selected for subsequent postsynthetic modifications ([2+2] cycloadditions or olefin metathesis) in case heteroligand complexes of type [Ag 3 ( L )( L′ )]X 3 ( L , L′ = A , B , C , D ) could be obtained with the olefins properly oriented . The trisimidazolium salts H 3 ‐ L (BF 4 ) 3 ( L=A – D ) were synthesized using slightly modified protocols of published procedures ,,. All trisimidazolium salts H 3 ‐ L (BF 4 ) 3 ( L=A – D ) were fully characterized by 1 H and 13 C{ 1 H} NMR spectroscopy, and mass spectrometry (see the Supporting Information).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… für [ 4 ‐Et](PF 6 ) 3 , Lit. für [ 6 ‐Et](PF 6 ) 3 und in den Hintergrundinformationen für [ 5 ‐Et](PF 6 ) 3 .) Da die drei Tris‐NHC‐Liganden identische Donorgruppen und eine sehr ähnliche trigonale Topologie aufweisen, besteht eine hohe Wahrscheinlichkeit für die Bildung von Heteroligand‐ oder oligomeren Reaktionsprodukten.…”
Section: Methodsunclassified
“…[6] Most of the metallosupramolecular host molecules are polynuclear Werner-type coordinationc ompounds in which the metal centers are coordinated by nitrogen and/or oxygen donor atoms of polydentate ligands. Recently,N -heterocyclic carbenes (NHCs) [7] have emergeda sanew class of ligands for the preparationo fm etallosupramolecular structures such as dinuclearm olecular rectangles, [8] molecular cylinders, [9] and organometallic polymers. [10] Amongt he coordination-driven supramolecular architectures, molecular squares are the moste xtensively studied derivatives startingw ith the pioneering work by Fujitae tal.…”
mentioning
confidence: 99%